2018
DOI: 10.3892/ol.2018.9677
|View full text |Cite
|
Sign up to set email alerts
|

HNF1B expression regulates ECI2 gene expression, potentially serving a role in prostate cancer progression

Abstract: Prostate cancer is the most common form of cancer in men, with increased incidence rates observed in older individuals. Prostate cancer is primarily driven via activation of the androgen receptor (AR), the principal transcriptional factor governing prostate cancer cellular programming and its associated metabolism. One of the downstream targets of AR is hepatocyte nuclear factor-1β (HNF1B), an important oncogenic transcription factor in prostate cancer. In the present study, the regulatory role of HNF1B in eno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
0
12
1
Order By: Relevance
“…The downstream interaction of HNF1B is currently poorly understood, but based on the animal model it has been suggested that the downregulation of HNF1B during tumor progression is associated with the upregulation of enoyl-CoA-(Δ) isomerase 2 (ECI2) protein levels, which is one of the possible downstream targets of HNF1B 31 . ECI2 represents one of the androgen receptor (AR) target genes 32,57 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The downstream interaction of HNF1B is currently poorly understood, but based on the animal model it has been suggested that the downregulation of HNF1B during tumor progression is associated with the upregulation of enoyl-CoA-(Δ) isomerase 2 (ECI2) protein levels, which is one of the possible downstream targets of HNF1B 31 . ECI2 represents one of the androgen receptor (AR) target genes 32,57 .…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, the authors compare HNF1B and ECI2 protein expression at different stages of prostate cancer development and concluded that during tumor progression, the protective effect of HNF1B is lost, and that is associated with an increased expression of ECI2 31 . The results of our study, compared to the only two previous studies concerning ECI2 in prostate cancer, similarly found an overexpression of ECI2 in the PC group, which was statistically significant in contrast to the low expression in AH samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HNF1B is a member of the HNF family, participates in regulating the metabolism of lipids, carbohydrates and proteins, and plays an important role in regulating hepatocyte differentiation and liver development 20 . Recent studies have shown that HNF1B has a significant correlation with the occurrence and development of various tumors, such as prostate cancer and pancreatic cancer 21 , 22 . In this study, we found that the expression of HNF1B was upregulated at different levels in BLCA, CHOL, KIRP, LIHC, STAD, THCA, and UCEC and downregulated in COAD, GBM, KICH, KIRC, and LUSC.…”
Section: Discussionmentioning
confidence: 99%